Media and representations of the economic crisis - Boubouka, Angeliki; Doudaki, Vaia (My University, 2019)
This chapter provides a short description of the media environment in Greece, with a special focus on the two newspapers studied, Ta Nea and I Kathimerini, by discussing their characteristics and challenges in the contemporary crisis context. The chapter includes also a part on the news media representations of the economic crisis by domestic and international media. These brief accounts aim to assist the contextualisation of the study in its mediated environment and related journalistic practices.
Keywords: Austerity; Journalism; Economic Crises